Septic Tenosynovitis of the Lower Extremity: A Case Report. Issue 4 (November 2022) - Garber, Hollie; Michel, Chris; Abdelmalek, George; Sudah, Suleiman; Kerrigan, Daniel J.; Dijanic, Christopher M.; Ali, Sayed
Category: Other Introduction/Purpose: Tibialis anterior rupture is an exceptionally rare complication of septic tenosynovitis. One case of septic tenosynovitis of TA has been previously documented by Lowell et al. 2020 It is worth noting in this case, that TA was unruptured. In this abstract, we present a case of TA rupture secondary to septic tenosynovitis. Methods: A 46-year-old female with a past medical history of depression, HIV, HCV, Diabetes Mellitus, medication noncompliance and current heroin abuse presented with 2 days of right ankle pain. She also reported fever, chills, diaphoresis, nausea and vomiting. She was diagnosed with right foot cellulitis based on clinical findings of erythema, induration and tenderness. She underwent computed tomography (CT) with contrast of her right lower extremity which showed a peripherally enhancing fluid collection surrounding the tibialis anterior tendon consistent with tenosynovitis. There appeared to be medial extension beyond the tendon sheath (Figure 1). A sagittal view is provided in Figure 2, which further demonstrates the fluid collection. Results: She had an I&D of the fluid collection and started on IV vancomycin. After admission to the medical floor, blood cultures were drawn. The patient failed to improve after 2 days of vancomycin therapy. The blood cultures were negative. She subsequently had MRI of her right lower extremity that showed a persistent peripherally enhancing fluid collection anterior to the tibialis anterior tendon and high-grade partial tear of the tibialis anterior tendon (Figure 3). She was then taken to the operating room for a repeat incision and drainage where the tendon sheath of the tibialis anterior was incised and the tendon was exposed with washout. Wound cultures were drawn, and afterward, her antibiotic regimen was broadened with Piperacillin-Tazobactam. She was taken back to the operating room a third time for primary closure of the wound. Wound cultures grew methicillin- sensitive Staphylococcus Aureus resistant to clindamycin and she was discharged on Bactrim. Conclusion: Septic or suppurative tenosynovitis is the infection and inflammation of the closed synovial sheath of a tendon. These infections typically involve the tendons and tendon sheaths of the flexor muscles in the hand. The potential spaces of tendon sheaths create a walled-off environment ideal for pathogens to grow in isolation from host defenses. he pathogenesis of septic tenosynovitis typically involves trauma from a laceration, puncture or bite but other cases of disseminated hematogenous spread have been reported (Newman et al., 1989). Both medical and surgical management is recommended for the best possible outcome.